Rancangan Sistem Akuntansi Untuk Meminimalisir Kesalahan Proses Pelunasan Hutang Atas Pembelian Raw Material - Annisa Febriyana Dewanti; Alfonsa Dian Sumarna (Jurnal Sistem Informasi Akuntansi (JASIKA), 2025)
This research aims to establish a standard operational procedure for settling trade payables related to purchasing raw material inventory, utilizing either flowcharts or narratives that implement the principles of reasonable internal control. This research method uses a qualitative method. The outcome of this research is a draft standard operating procedure for settling trade payables for the purchase of raw material inventory at PT PI, including a flowchart, narrative, and transaction documents that implement the principles of reasonable internal control.